2009
DOI: 10.1007/s00405-009-0924-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of autologous fascia in unilateral vocal fold paralysis

Abstract: The objective of this retrospective clinical review was to evaluate the long-term results of injection laryngoplasty with autologous fascia as a single, primary procedure in unilateral vocal fold paralysis. Forty-three patients who had undergone injection laryngoplasty between 1996 and 2003 entered the study. Clinical examination and videostroboscopy were performed and the voice handicap index was analyzed postoperatively. Pre- and post-operative evaluation included computerized acoustic analysis and perceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
8
0
3
Order By: Relevance
“…In a similar study by Reijonen et al, most voice parameters significantly improved after injection laryngoplasty with autologous fascia (13). In another study by Rihkanen et al, video analysis revealed fewer large glottal gaps after augmentation with autologous fascia (14).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a similar study by Reijonen et al, most voice parameters significantly improved after injection laryngoplasty with autologous fascia (13). In another study by Rihkanen et al, video analysis revealed fewer large glottal gaps after augmentation with autologous fascia (14).…”
Section: Discussionmentioning
confidence: 83%
“…Use of autologous fascia, harvested from the fascia lata, has been shown to be more effective than other materials (eg, autologous fat, collagen, calcium hydroxylapatite, Gelfoam™, and hyaluronic acid), considering its lower metabolic requirements, more stability, and less susceptibility to resorption (12,13). However, advantages of this material have been less examined in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Reijonen ve ark. ise, 3-10 yıl gibi, uzun dönem takipte fasyanın stabil kaldığını tespit etmişlerdir [26].…”
Section: Otolog Fasyaunclassified
“…Resorption may be an advantage if temporary medialization is required however often over-injection of these substances is necessary to ensure reasonable length of efficacy and can temporarily compromise the airway. Autologous fascia has been used with long-lasting results (3-10yr) but requires separate incision to harvest the fascia 6,7 . Bioplastique is a biphasic combination of solid silicone particles suspended in polyvinylpyrrolidone carrier.…”
mentioning
confidence: 99%